Unlocking Potential: Rethinking MBKM Curriculum Reformation with Constrained Resources in Arabic Education Study Program - Rifa'i, Ahmad; Muslimah, Maziyyatul (Institut Agama Islam Negeri Curup, 2024)
This research aimed to elucidate the transformative process and constraints undergone by the Arabic Language Education study program at the State Institute of Islamic Studies Kediri, in response to the Ministry of Education's mandate for a more inclusive, forward-looking, and outcome-driven higher education curriculum, the MBKM (emancipated curriculum). It presented a dynamic and adaptable framework designed to foster creative learning and diverse student needs. Embracing this concept poses both an opportunity and a challenge for universities. This study used qualitative approach and employed documentation as well as focus group discussion to investigate the curriculum reform at Arabic Language Education study program and provide practical guidance for institutions facing similar challenges, serving as a valuable resource to enhance graduates' employability in Arabic language education. The findings of this study revealed that: 1) FGD was selected as a transformation technique because of its efficacy and efficiency; 2) During the curriculum reform, Arabic Language Education study program encountered procedural issues related to student exchange activity, a lack of prior collaboration agreement, and a limited budget; 3) The study program strategically adopted Integrative Curriculum that yet adheres to the MBKM values, involving carefully scrutinizing the KKNI format, adjusting relevant areas, refining teaching and learning methodologies, and introducing a transformative off-campus internship program for students that lasted a whole semester; 4) The Integrative Curriculum found to retain the values of the MBKM curriculum, emphasizing; learning activities outside the classroom, projects fostering independent thinking, internships to bridge educational and industrial needs, differentiated learning with elective courses tailored in career paths.